Gliding lizards use the position of the sun to enhance social display. (February 2017) - Klomp, Danielle A.; Stuart-Fox, Devi; Das, Indraneil; Ord, Terry J.
Abstract : Effective communication requires animal signals to be readily detected by receivers in the environments in which they are typically given. Certain light conditions enhance the visibility of colour signals and these conditions can vary depending on the orientation of the sun and the position of the signaller. We tested whether Draco sumatranus gliding lizards modified their position relative to the sun to enhance the conspicuousness of their throat-fan (dewlap) during social display to conspecifics. The dewlap was translucent, and we found that lizards were significantly more likely to orient themselves perpendicular to the sun when displaying. This increases the dewlap's radiance, and likely, its conspicuousness, by increasing the amount of light transmitted through the ornament. This is a rare example of a behavioural adaptation for enhancing the visibility of an ornament to distant receivers.